Youth itineraries, individuation, and reflexivities: approaches to social participation in low-income metropolitan neighborhoods - Pinheiro, Leandro R. (Emerson de Pietri, 2023)
This study analyzes individuation itineraries by considering the forms of participation and reflexivity of young people who live in low-income neighborhoods in three metropolitan areas: Buenos Aires/Argentina, Porto Alegre/Brazil, and Santiago/Chile. For this, this study articulated the results of several empirical studies conducted from 2013 to 2019 with the conceptual tools in Danilo Martuccelli’s sociology of the individual, especially its notions of tests, supports, and social textures. This research first addresses theoretical frameworks to implement its problem and methodological strategies to build and analyze youth’s narratives. Then, it interpreted its data corpus around two central axes: a) low-income territories, actors, and interworlds and b) young people, social participation, and reflexivities. Young people face a plurality of material and symbolic coercions in several low-income territories. However, these territories also create collective spaces in which youths establish personal and group identifications as they discover or generate sports, artistic-political, and educational proposals, which create intergenerational bonds, recover ancestral knowledge, and build referential and reflective landmarks, transforming territorialities into supports and a sign of recognition. Thus, studying youth narratives offers a privileged tool to analyze Latin American low-income agencies and individualities.
Itinerarios juveniles, individuación y reflexividades: aproximaciones a la participación social en barrios metropolitanos populares
Keywords: Individuación; Itineraries; Reflexividades; Participación social; Juventud